Impact of religious fasting on ocular dryness: objective and subjective assessment - Alomari, Amal F.; Issa, Sara; Musleh, Asma; Abusamak, Mohammad; Bdair, Omar; AlRyalat, Saif Aldeen; Al-Wakfi, Alanoud; Jaber, Mohammed; Alloubani, Ahmad; Sahawneh, Haitham; El-Faouri, Muhannd; Abdul Aziz, Ayman; et al. (Frontiers in Medicine, 2025)
BackgroundCertain religions require long hours of fasting, abstaining from fluid intake for durations extending up to 16 h. Lack of fluid intake may alter multiple physiological parameters, which can influence the ocular system. In this prospective study, we evaluated the effect of prolonged fasting on dry eye disease using both objective and subjective measures.MethodsWe included patients who fasted for at least 12 h a day for at least 2 weeks, including the testing day, and retested them at least 1 week after the fasting period had ended with no fasting on the testing day. At each visit, Non-Invasive Keratograph Break up time (NIKBUT) and Tear meniscus height (TM) were measured using the Oculus Keratograph 5 M. Ocular Surface Disease Index (OSDI) was evaluated at each timepoint to assess dryness symptoms subjectively.ResultsThis study included a total of 40 patients. NIKBUT values during the fasting times were higher than during the non-fasting times; however, the difference was statistically non-significant. There were no significant differences in TM and OSDI measurements between non-fasting and fasting periods (p > 0.05). Lubricating eyedrop use was significantly lower in fasting patients.ConclusionOur study showed that prolonged fasting, including complete abstinence from fluid intake, did not lead to significant dryness, neither subjectively nor objectively. During fasting, patients used significantly fewer lubricating drops compared to non-fasting periods.